KOMUNIKASI ISLAM DALAM PEMBANGUNAN MORAL DAN SOSIAL: STUDI DAKWAH DIGITAL AKUN INTAGRAM @GUSBAHAOFFICIAL - Kustiawan, Winda; Sahlaya, Muhammad Rishan; Attaya, Muhammad Fairuz; Naufik, Ibrahim; Alfiris, Rizky Rahman (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Islamic communication is a strategic effort in conveying moral and social messages sourced from the Qur'an and Sunnah. The development of the digital era has brought new challenges in moral and social development, especially among the millennial generation. Content on social media often leads to moral decadence due to the lack of educational and meaningful narratives. Therefore, digital da'wah is an effective solution in facing this challenge by offering Islamic values that are relevant, contextual, and easy to understand. This research aims to identify the Islamic communication strategy applied by @Gusbahaofficial Instagram account in shaping the moral and social of the younger generation. Using a descriptive qualitative approach, this research analyzes the content of the account's uploads. The results show that qaulan baligha, and al-bayan-based Islamic communication strategies are used effectively through attractive visuals, casual but meaningful narratives, and supporting Qur'anic arguments. This strategy, combined with the tazkiyah or soul cleansing method, proved to be able to move the audience to introspection and contribute to the formation of social solidarity. This approach emphasizes the important role of digital da'wah in bridging Islamic values with modern life, so that it can become a strategic medium in building individual morality and social collectivity in the digital era.